Dynamic changes in the endophytic bacterial community during maturation of Amorphophallus muelleri seeds - Yang, Min; Qi, Ying; Liu, Jiani; Wu, Zhixing; Gao, Penghua; Chen, Zebin; Huang, Feiyan; Yu, Lei (Frontiers in Microbiology, 2022)
Abstract: The seed microbiota is considered to be the starting point of the accumulation of the plant microbiota, which is conducive to the preservation and germination of seeds and the establishment and development of seedlings. Our understanding of the colonization and migration dynamics of microbial taxa during seed development and maturation is still limited. This study used 16S rRNA high-throughput sequencing to investigate the dynamic changes in the composition and diversity of the endophytic bacterial community during the maturation of Amorphophallus muelleri seeds. The results showed that as a seeds grew more maturematured (green to red), the Shannon index of their endophytic bacterial community shrank first decreased and then grewincreased, and the ACE and Chao1 indicesex of the endophytic bacterial community in it decreased gradually. The Shannon, ACE, and Chao1 indices of the endophytic bacterial community in the seed coat first decreased first and then increased. Principal coordinate analysis of the bacterial communities revealed that the seed coat at different maturity stages showed significantly separated distinct bacterial communities and formed different clusters according to maturity stage. The bacterial communities of green and red seeds showed a clear separation, but they both overlapped with those of yellow seeds, indicating that some core taxa were present throughout seed maturation, but their relative abundance was dynamically changing. As the seedseeds grew more mature, the relative abundance of some bacterial communities with plant growth-promoting traits and others correlated with plant resistance (e.g., Burkholderia-Caballeronia-Paraburkholderia, Bacillus, Pseudomonas, Bradyrhizobium, Streptomyces) tended to increase and peaked in fully mature seeds and seed coats. The endophytic bacterial community of A. muelleri seeds seems to be driven by the seed maturation state, which finding can provide a theoretical basis for a comprehensive understanding of the assembly process of the microbial community during A. muelleri seed maturation.